Consumer Racial Profiling and Perceived Victimization: A Phone Survey of Philadelphia Area Residents - Gabbidon, Shaun L. (American journal of criminal justice, 2007)
This paper explored the perceived prevalence of consumer racial profiling (CRP) (also known as “Shopping While Black”) among residents in Philadelphia. Based on data collected from a random digit dialing (RDD) phone survey, the authors examined the characteristics of those persons who believed they had been profiled in retail establishments. The research found that African Americans were ten times more likely than non-African Americans to believe they had been profiled in a retail establishment. As for gender differences, males were nearly two times more likely than females to report that they had been experienced CRP. Educated respondents were more likely than those with less education to report having experienced CRP. There were no significant findings regarding income. The authors conclude by noting the policy implications of the research findings.